Der Amerikanische freund - Wenders, Wim.; Hopper, Dennis, 1936-; Ganz, Bruno, 1941-; Highsmith, Patricia, 1921-1995.; Road Movies Filmproduktion; Anchor Bay Entertainment (Firm) (Troy, MI : Anchor Bay Entertainment, 2002)
Story about a Hamburg picture framer who is perfectly ordinary except that he is suffering from a rare and fatal blood disease. His peace and sanity are upset when he is offered money to assassinate a Mafia figure in Paris.
DVD.
In German with optional English subtitles.
Not rated.
Dennis Hopper, Bruno Ganz, Lisa Kreuzer, Gerard Blain.
Directed by Wim Wenders ; photography, Robby Muller ; edited by Peter Przygodda ; music, Jurgen Knieper.
Originally released in 1977 as a motion picture.
Keywords: Detective and mystery films; Feature films